Determinants of Carbon Emission Disclosure in Energy Sector Firms Listed On the Indonesian Stock Exchange - Amalinda Kartika; Zuhrotul Isnaini (Citakonsultindo, 2024)
This study aims to examine and gather empirical data regarding the impact of profitability, leverage, board of directors size, board of commissioners size, and appropriate proper rating on the carbon emissions disclosure by energy sector firms listed on the Indonesia Stock Exchange from 2019 to 2022. The sample for this research comprised 82 energy sector companies publicly traded on the Indonesia Stock Exchange. A purposive sampling method was employed in the research study to select a sample of 48 companies for observation. This research uses content analysis techniques and documentation of the organization's sustainability and financial reports spanning the subsequent four years to quantify carbon emissions. Descriptive statistics and multiple linear regression analysis were employed to analyze the data, utilizing version 16.0 of the Statistical Package for the Social Sciences (SPSS) software. The study indicates that leverage significantly and positively influences carbon emission disclosure. There is no statistically significant positive correlation between profitability, board of commissioners size, profitability, and proper rating about carbon emission disclosure.